The Relationship Between Good Corporate Governance and Transfer Pricing in Multinational Mining Industry Companies Listed on the Indonesian Stock Exchange (Idx) Period 2018-2022 - Safira Kirana Riawan (Politeknik Ganesha Medan, 2026)
This research aims to determine the relationship between good corporate governance (GCG) and transfer pricing in mining industry multinational companies. In this research, good corporate governance used is foreign ownership and audit quality. Foreign ownership is measured by comparing the number of shares owned by foreign parties with the total shares outstanding then multiplied by 100% and audit quality using a dummy variable which has a value of 1 if the financial report is audited by The Big Four KAP and a value of 0 if the financial report is not audited by KAP The Big Four. The sample in this research is a mining industry multinational company listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. This research uses a sampling method in the form of purposive sampling using secondary financial report data. The results of this research show that foreign ownership has an insignificant effect on transfer pricing of mining industry multinational companies and audit quality has a significant negative effect on transfer pricing of mining industry multinational companies. Keywords: Transfer Pricing, Foreign Ownership, Audit Quality